Types of Social Modeling in the Content of the Course of Choice «Socio-Educational Activities Under the National School: Problems» - Kliui, Liubov (Pedagogical Discourse, 2015)
The article deals with the types of social simulation used in the professional activity of the social teacher in the course of the selection of the content of the psychological and pedagogical disciplines. It is proved that the content of school subjects in the social sector of the philological-humanities and art-aesthetic areas can be integrated with programe-minimum single rate philology. Examples of tasks aimed at the management, diagnostics and forecasting of socio-educational mechanisms and cited in the authorʼs optional courses «Socio-educational activities under the national school: problematic issues» in the content of the psychological-pedagogical training of future social workers. An example of simulation in the sense of the authorʼs optional course «Socio-educational activities under the national school: problematic issues» in the sense of psychological and pedagogical training of future social workers is the method of choice and solutions: a) in a professional situation; b) in the process solutions and evaluation tasks; c) the formulation of strategies at the limited information on the conditions for further development. Modeling understood as a process of creating complex simulation systems, which are developed in parallel evolution of the object model and is the result of a condition, or new ways of communication and control. It is proved that the simulation of socio-educational processes contributes to the improvement of social management, the use of the system in its methods. Cultural foundations of social pedagogy of the information society are reviewed and interpreted as contents filling of social pedagogical science in education with the achievements of national and world cultures and the basics for the transformation of the system of social and pedagogical impact. Examples of tasks aimed at managing, diagnosing and predicting social and educational mechanisms are given. The examples of tasks are suggested in the authorʼs elective course «Social and educational activities in terms of national school: areas of concern» in view of psychological and pedagogical training of future social care teachers. It is proved that the content of the psychological and pedagogical training of future specialists of simulation should be based on predictions of new combinatorial conditions and trends in the various spheres of public life, contributing to a high level of practical activities undertaken by specialists of pedagogical and social spheres.